GroupLead Group facilitation in language teacher education - Szesztay, Margit; Bolitho, Rod; Einhorn, Meg; Council of Europe; European Centre for Modern Languages(ECML) (Strasbourg : Council of Europe, 2007)
The aim of this is to provide an introduction to what working with groups in a facilitative mode involves. The intended audience is mentors and trainers working with groups of language teachers. Although the material is sequenced starting with background and principles and moving on to practical application, users can pick and choose from it based on interests, needs, and past experiences with facilitation. It is divided into eight sections and organised around eight thematic areas.
"The overall title of the ECML's 2nd medium-term programme (2004-2007) is Languages for social cohesion - language education in a multilingual and multicultural Europe."--Packaging.
System requirements: PC; Windows; CD-ROM drive; media player; ability to open .pdf files.
Keywords: Languages, Modern -- Study and teaching -- Europe; Language and languages -- Study and teaching -- Europe; Language teachers -- Training of -- Europe